Periodisation of recovery strategies for Celtic league professional rugby union - Harrington, B. (Journal of Australian Strength and Conditioning, 2016)
The following report is an attempt to establish best practice for recovery strategies within professional rugby union (rugby). This report has been complied based on the current literature available. Throughout this report every attempt has been made to ensure all practical applications are based on peer-reviewed evidence. Following an extensive review of existing literature and a needs analysis of the demands of the playing and training demands placed on professional rugby players it was decided that a one size fits all approach could not be applied and that depending on the specific goals of the various stages of the season a periodised recovery plan was required.